2009
DOI: 10.1109/tmag.2009.2029635
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Vibration Suppression in Hard Disk Drives Using Instrumented Suspensions

Abstract: This paper summarizes work that has been completed to evaluate the use of high-resolution thin-film strain sensors for vibration suppression in hard disk drives (HDDs). In particular, we demonstrate the viability and necessity of symmetrical sensors for cancellation of common non-off-track modes in the measurement. Thin-film ZnO strain sensors have been successfully integrated into instrumented suspension prototypes, and strain signals were extracted from operating disk drives. High-resolution strain sensing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Other hardware modifications for the servo have been proposed such as instrumented suspensions for active damping of vibrations [90], [91], and accelerometers for feedforward compensation of shock and vibration [92]. So far it appears that performance improvements offered by instrumented suspensions have not justified their cost.…”
Section: Improving Tracking Performancementioning
confidence: 99%
“…Other hardware modifications for the servo have been proposed such as instrumented suspensions for active damping of vibrations [90], [91], and accelerometers for feedforward compensation of shock and vibration [92]. So far it appears that performance improvements offered by instrumented suspensions have not justified their cost.…”
Section: Improving Tracking Performancementioning
confidence: 99%
“…Lately, owing to high flexibility, fast response, high sensitivity, broad frequency bandwidth, high dynamic range, low cost and ease of processing, piezoelectric sensors have found a large number of applications in wearable electronics [26][27][28][29], medical equipment [30,31], structural health monitoring [32][33][34][35][36], machining process monitoring [37][38][39][40][41], structural parameter measurement [42][43][44][45], surface acoustic wave detection devices [46], hard disk drive [47,48] and microphones [49]. The development history of piezoelectric sensor applications in recent years is shown in Figure 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the additive and subtractive wafer-level processes involved with thin-film fabrication are similar to those used in existing stateof-the-art suspension fabrication. Felix et al [11] described the implementation of thin film sensors in feedback control with a VCM only. The results demonstrated that minimal performance improvements could be achieved with the VCM actuator alone.…”
Section: Introductionmentioning
confidence: 99%